KAJIAN KESIAPSIAGAAN MASYARAKAT DALAM MENGHADAPI BENCANA GEMPABUMI DI DESA BAWURAN, KECAMATAN PLERET KABUPATEN BANTUL - , Badrudin ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The community preparedness is absolutely necessary in order to sensure a positive response if a disaster occurs. The condition of preparedness in the community of Bawuran Village in overcoming the disaster is dynamic in nature, which means that there will be some sort of increment and decrement. Such circumstances needs to be researched in order to monitor and to find the condition of preparedness in overcoming the earthquake. The research is aimed to analyze the influence of communityâs knowledge about earthquake toward the a attitude to decrease the risks of earthquake, to encounter and to identify the action that the community perfoms in order to decrease the risk of earthquake and to analyze the communityâs level of preparedness in overcoming the earthquake. The researcher employed combined research methods by mean of qualitative and quantitative approach. The researcher gathered the data by mean of questionaire, observation, and study of documentation. The result of the research showed that there was a significant influence between the communityâs level of knowledge about earthquake and the effortto decrease the risk of earthquake. The implementation of structural and non-structural mitigation effort performed by the community and the villave authority do not operate independently: instead, the implementation is facilitated by the external party that encouraged the activities of decreasing the risk of earthquake in village Bawuran. The level of community preparedness was still low in preparing themselves to overcome the earthquake